Production of Enzyme for Pleurotus pulmonarius by Solid-State Fermentation on Peach-Palm and Cocoa Waste - Santos, Mateus Pereira Flores; Bezerra, Camila Oliveira; Casteliano, Geni Alves; Uetanabaro, Ana Paula Trovatti; Silva, Erik Galvão Paranhos da; Costa, Andréa Miura da (Fine Chemical Engineering, 2025)
Agro-industrial waste, which is generated during the process of food production, has the potential to contaminate significant quantities of natural resources. Concurrently, the cultivation of edible mushrooms from waste materials that have been previously discarded is undergoing exponential growth. This is due to the nutritional value of the mushrooms and their biotechnological potential in the production of enzymes of industrial interest. The present study aims to evaluate the production of lignocellulolytic and hydrolytic enzymes by the edible mushroom Pleurotus pulmonarius on cocoa and peach-palm wastes, with or without the addition of cocoa bean film (CBF) as a growing medium. The solid-state fermentation methodology was employed, with the proportion of CBF varying between 0, 10 and 20% for a duration of 5, 10 and 15 days at 28 °C. The enzymatic activities of amylase, xylanase, pectinase and laccase were analysed. For amylases, the most optimal results were achieved through the utilisation of cocoa residue, yielding a maximum activity of 97.16 U/g (0% CBF and 10 days of fermentation). In the case of xylanase, pectinase and laccase, the optimal activities were observed with peach-palm waste, with levels of 29.01 U/g (20% CBF and 5 days of fermentation), 26.25 U/g (10% CBF and 5 days of fermentation) and 3.98 U/g (0% CBF and 15 days of fermentation), respectively. The results obtained demonstrate the efficient utilisation of this waste for the production of microbial enzymes with potential biotechnological applications. This is achieved through the employment of cost-effective techniques to yield high-value-added outputs.